Understanding public awareness of fall epidemiology in the United States: A national cross-sectional study - Sheridan Elizabeth; Wiseman Jessica M.; Quatman Carmen E. (Open Health)
Falls are a leading cause of death and disability for adults aged 65 and older, despite the availability of evidence-based interventions to decrease fall risk. We sought to assess public awareness of falls in the United States (US), including when falls are most likely to occur.